A Note on the Effect of Storage on Physicochemical Properties of Baobab (Adansonia digitata L.) Seedsʼ Oil from Kordofan and Blue Nile States (University of Khartoum Journal of Agricultural Sciences, 2022)
Baobab (Adansonia digitata L.) is an indigenous forest tree related with the Savannah dry lands of sub-Saharan Africa. Local communities utilize the leaves, pulp, and seeds of Baobab as a source of nutrition and for income generation. Seed oil has been used for centuries by rural communities as food and medicine. The global demand for Baobab seed oil in industrial applications has increased in recent years. The present study was conducted to determine physicochemical properties, mineral content and effect of storage on seeds from two different geographical locations (Kordofan and Blue Nile States). Six different samples of Baobab seeds were collected, prepared and stored in 2017 at room temperature until analysis in 2019. The oil was extracted by cold pressing process and its physicochemical properties were evaluated by standard and established methods. The results showed that the Baobab oil color was golden yellow/ reddish yellow and it showed resistance to change in color and seeds contained reasonable amount of oil. Oil density, PH, refractive index and acid value showed negligible change with the storage. However the peroxide value increased when the storage period increased, while the iodine value, saponification and viscosity of the oil decreased markedly with the storage time. Kordofan seed oil was higher than Blue Nile in density, oil content and saponification value, while Blue Nile seed oil showed higher viscosity, peroxide value and minerals especially potassium content.
Keywords: Baobab oil; physicochemical properties; oil content; saponification value; mineral content